Increase in urinary markers during the acute phase reflects the degree of chronic tubulointerstitial injury after ischemia-reperfusion renal injury. (2nd January 2017) - Hisamichi, Mikako; Kamijo-Ikemori, Atsuko; Sugaya, Takeshi; Ichikawa, Daisuke; Hoshino, Seiko; Hirata, Kazuaki; Kimura, Kenjiro; Shibagaki, Yugo
Abstract: Context : Acute kidney injury (AKI) could lead to progressive chronic kidney disease (CKD).Objectives : To demonstrate that urinary markers in AKI are associated with the degree of persistent renal injury.Material and methods : Human L -FABP chromosomal transgenic ( T g ) mice were subjected to ischemia-reperfusion (I/R) clamping renal pedicle for 20 min or 30 min. Kidneys were obtained at one and 40 days after I/R.Results : Urinary L -FABP, NGAL, Kim-1 and albumin levels increased during the acute phase and were significantly correlated with the degree of tubulointerstitial fibrosis during the chronic phase.Discussion and conclusion : These markers could detect higher risk of progression to CKD.